The Effects of Trade Wars on World Welfare - AYDIN, Rahman; LÖGÜN, Anıl; ALPAGUT, Serhat; AYDIN, Buket (International Journal of Contemporary Economics and Administrative Sciences, 2021)
In this study, the effect of trade wars on global welfare is investigated. It is known that the USA and China mutually increased the data rates applied to some imported products. If many commodity groups are included in the trade wars, it is a matter of curiosity how the welfare level will be affected. In this study, the effects of restrictions or tax increases applied by countries on imported goods on welfare are examined. For this reason, we aimed to look at the trade wars between the world’s largest economies, the USA and China, over some goods from a broad perspective. We also expanded our research and included the European Union, which is an important economic power, together with the USA and China. Thus, we aimed to investigate the impact of a possible trade war between the world’s largest economies on both the welfare of the countries and the global welfare. According to the results we have obtained, trade wars negatively affect both the welfare level of countries and the global economy.